Pengalaman Self Regulated Learning Pada Mahasiswa Dalam Menghadapi Ujian Tengah Semester Secara Daring - Rijal Abdillah; Afra Refancienna Subakuh; Tazkiya Nazla (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The implementation of the midterm exam, which is currently being conducted online in the midst of a hybrid makes the use self-regulated learning different from when the learning system and midterm exams are conducted offline on campus. The difference in the current system will certainly affect the self-regulated learning of students. From this, students will have different experiences when they will undergo self-regulated learning as preparation for the midterm exam. This experience will be explored more deeply in this study by using qualitative methods and phenomenological approaches that will describe more deeply what is experienced with 2 students as research informants while undergoing self-regulated learning midterm examonline. From the results of the study, it was found that there was use of study time, learning motivation, learning strategies and feelings of anxiety and difficulty from the experiences of the subjects when doing self-regulated learning in order to face the midterm exams.